ANALYSIS OF MARKETING CHANNELS RAMBUTAN CROP SEEDS (Case Study: Kelurahan Kebun Lada, Kec. Binjai Utara, Kotamadya Binjai) - Surna Herman; Khairunnisa Rangkuti; Muhammad Novriyansah Harahap (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The purpose of this study were (1) To determine the pattern of channels and marketing costs of plant seeds rambutan in the area of research, (2) To determine the marketing functions performed by each institution in the area of research, and (3) To determine the efficiency of marketing rambutan plant seeds in the study area. Sampling method using census method that is the entire population of the research sample. The analytical method used is descriptive analysis based on surveys and observations made in the study area. From the research that has been done, there are two marketing channels seedlings of fruit crops in the area of research. Profit margin marketing channel pattern 1 is Rp. 4,680 / polybag and profit margin marketing channel pattern 2 is Rp. 6,393,5 / polybag. Marketing functions are performed on the first line is the manufacturer to the sales function. While retailers carry out the functions of purchase, sale, transportation, storage, financing and market information collection. And on the second line pattern manufacturers perform the functions of sales, storage, financing and underwriting risk. Both have efficient marketing channel that is where one marketing channel has a value of 39.1% and the efficiency of marketing channels 2 having an efficiency value of 36.1%